2022
DOI: 10.1111/apha.13767
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of microRNAs in VIP+ interneurons impairs olfactory discrimination and decreases neural activity in the olfactory bulb

Abstract: Aim: MicroRNAs (miRNAs) are abundantly expressed in vasoactive intestinal peptide expressing (VIP + ) interneurons and are indispensable for their functional maintenance and survival. Here, we blocked miRNA biogenesis in postmitotic VIP + interneurons in mice by selectively ablating Dicer, an enzyme essential for miRNA maturation, to study whether ablation of VIP + miRNA affects olfactory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 90 publications
(226 reference statements)
0
7
0
Order By: Relevance
“…Moreover, tetrode single unit recordings from the M/T layer after Dicer ablation in VIP+ INs in awake head‐fixed mice demonstrated decreased odour‐evoked firing in M/Ts. Finally, Wu et al 1 showed that Dicer ablation restricted to the OB produced similar results.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, tetrode single unit recordings from the M/T layer after Dicer ablation in VIP+ INs in awake head‐fixed mice demonstrated decreased odour‐evoked firing in M/Ts. Finally, Wu et al 1 showed that Dicer ablation restricted to the OB produced similar results.…”
mentioning
confidence: 84%
“…This is an interesting and relevant topic related to how genes affect brain circuits and behaviour in health and disease. In the present volume of Acta Physiologica , Wu et al 1 addressed this question using a multi‐technique approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The animal training and behavioral tasks were carried out using methods similar to our previous studies (Wang et al, 2022 ; Wu et al, 2022 ). For fiber photometry recordings, head-fixed mice were trained on an air-supported free-floating Styrofoam ball which allowed the mice to maneuver.…”
Section: Methodsmentioning
confidence: 99%
“…To explore the influence of cholinergic neurons' inactivation on odor discrimination, we conducted an odor discrimination assay that lasted for 9 days, including the training period (2 days), the easy task (3 days), and the difficult task (4 days) in freely moving mice. As in our previous study (Sun et al, 2019;Wang et al, 2022;Wu et al, 2022), mice were first trained to undergo a go/go task, then the mice were trained to perform a go/no-go task, including the easy task (S+: isoamyl acetate; S−: 2-heptanone) and a difficult task (S+: isoamyl acetate: 2-heptanone = 6:4; S−: 2-heptanone: isoamyl acetate = 6:4; Figure 7E). The percent correct rate during the go/no-go task was compared between experimental (Gi + CNO) and control (Gi + saline, mCherry + CNO) animals.…”
Section: Inactivation Of Hdb Cholinergic Neurons Impairs Odor Discrim...mentioning
confidence: 99%